Observational data-based sequence stratigraphy of a clastic wedge within an active foreland basin, Spirit River Formation, west-central Alberta, Canada. (June 2022) - Newitt, Dillon Jared; Pedersen, Per Kent
Abstract: The Spirit River Formation forms a third-order clastic wedge that consists of strongly progradational to aggradational parasequence sets following a maximum transgression. This observed parasequence stacking pattern is opposite from the traditional sequence stratigraphic models following a maximum marine transgression. The previously recognized gas-charged but low permeability reservoir sandstone bodies of the progradational succession were disregarded as it has required the recent technological advancement of horizontal wells with multistage hydraulic fracturing to exploit them. The unusual parasequence stacking pattern of the progradational succession was unraveled by detailed logging of 10's of cored intervals and 1, 000's of wells with log suites for facies analysis and sequence stratigraphy. Evaluation of the local basin controls on parasequence set stacking patterns shows a high sediment influx relative to the available and rate of creation of new accommodation space relationship controlled the initial strongly progradational stacking pattern of the lower part of the Spirit River Formation. A high sediment influx was maintained, but a significant increase in accommodation from increased tectonic activity and associated subsidence resulted in the overlying strongly aggradational parasequence set stacking pattern of the upper part of the Spirit River Formation. Understanding the local basin controls on sedimentation and accommodation that helps predict parasequence set stacking patterns leads to better unconventional exploration and exploitation opportunities worldwide of clastic wedges. Highlights: Sequence stratigraphic framework of the Spirit River Formation clastic wedge. Foreland basin controls of rate of sediment flux and accommodation creation on parasequence set stacking patterns. Conventional and unconventional petroleum plays depend on basin conditions.